استخدام الانترنت و علاقته باللامعيارية عند الطلبة الجامعيين دراسة ميدانية بجامعة محمد خيضر بسكرة - إيمان, نـوي (Sciences humaines, 2014)
الملخص : هدفت هذه الدراسة إلى التعرف على استخدام طلبة جامعة بسكرة للإنترنت و علاقة هذا الاستخدام باللامعيارية عندهم ,من خلال استطلاع آراء عينة من طلبة الجامعة بلغ تعدادها (400) مبحوثاً و مبحوثه، تم اختيارها بطريقة كرة الثلج . أظهرت نتائج الدراسة بأن معدل استخدام الإنترنت من قبل طلبة جامعة بسكرة يفوق المتوسط  يزداد في حالة استخدام الطلبة للإنترنت بمفردهم، وكلما زاد عدد ساعات الاستخدام اليومي. كما أظهرت النتائج بأن طلبة مفراد عينة الدراسة تعاني من اللامعيارية بمتوسط حسابي قدر2.87 . كما أشارت النتائج، كذلك، إلى عدم  وجود علاقة بين استخدام الإنترنت واللامعيارية حيث قدرت العلاقة باستعمال معامل الارتباط بيرسون ب 0.034 .                                      Abstract  : The purpose from this study to identify the students' use of internet in  the University of Biskra and its relationship with Ballamaaaria on them (students), through a survey of  400 students  by applying the selection in manner snowball. Results of the study showed that the rate of Internet use by students of the University of Biskra above-average increases in the case of students use the Internet on their own, and the number of hours of daily use increases. The results also showed that students Mfrad the study sample suffering from Allamaaaria a mean as much as 2.87. The results also indicated, as well, to the absence of a relationship between the use of the Internet and in terms Allamaaaria estimated relationship using the Pearson correlation coefficient 0.034.